Biological Weapon or Biological Threat? - Vladyko, A. (Journal of Environmental Science and Engineering Technology, 2019)
A hundred years have passed since viruses were first discovered and throughout this time humans overwhelmingly regard them as agents of infectious diseases. Based on the previously developed concept (1997) on the role of viruses in the origin and evolution of biological kinds, we found it necessary to discuss another point of view pertaining to the biological nature and function of viruses. Adaptogens are structures similar to a virus but differ from it by disseminated format in the macro organism by the principle of mixed co-viral system are proposed for consideration as a biological complex of molecular motifs designed to adapt humans, animals, plants, bacteria (essentially all flora and fauna) to changing environmental conditions to maintain species diversity. From this standpoint a virus is regarded as a consequence of environmental effects on adaptogens, and serves as an indicator or marker of disease rather than a factor of evolution. In this regard, we propose to revise the established provisions for the diagnosis, prevention and therapy of infectious and somatic diseases as well as the classification of viruses.